Large enhancement in the magnetostriction parameters of the composite of CoFe2O4 and CoFe1.9Ga0.1O4 - Anantharamaiah, P. N.; Joy, P. A. (Materials Letters, 2019)
A new strategy to enhance the magnetostriction parameters of cobalt ferrite (CoFe2O4) is illustrated. A composite comprising of nanocrystalline CoFe2O4 and bulk CoFe(1.9)Ga(0.1)O(4 )powders were mixed together then compacted and sintered at 1450 degrees C for 10 min. For a composite of 70 wt% CoFe2O4 and 30 wt% of CoFe(1.9)Ga(0.1)O4, maximum magnetostriction coefficient (lambda(max)) of -350 ppm has been obtained at lower magnetic field which is nearly 20% and 65% higher than that obtained for CoFe2O4 and CoFe1.9Ga0.1O4, respectively. Moreover, the composite exhibited higher strain sensitivity [d lambda/dH](max )of -2.6 x 10 (9) A(-1) m against the individual components of the composite. (C) 2018 Published by Elsevier B.V.
Keywords: Ceramics; Composite materials; Magnetic materials